Metacognitive Awareness in Students - Rinaldi, Rinaldi; Rahmatillah, Febriani (Jurnal Neo Konseling, 2022)
This study aims to measure students' metacognitive and the difference in abilities used from the metacognitive component. The research subjects were 500 Padang State University students. The research measurement tool uses the Metacognitive Awareness Inventory from Schraw and Dennison. The results showed that metacognitive awareness was in the moderate category at 36.4%. While the results of the metacognitive awareness research component of cognition knowledge in the medium category amounted to 37.6%, the component of cognition regulation in the high category was 31.6%. The results showed that metacognitive awareness based on gender was 39.08% for men, while 34.66% for women. The results showed that metacognitive awareness based on gender components of cognitive knowledge in the medium category for men was 43.10%, while women were 33.13%, components of cognition regulation in men were in the high and medium categories of 34.48%, while women in the medium category were 33.44%. There is no difference in metacognitive abilities between men and women. There is a correlation between metacognitive abilities and academic achievement.